The Odessa Years: Shoshana Persitz and the Gamliel Library of Omanut Press (1918-1920) - Brener, Ann (Judaica Librarianship, 2017)
Shoshana Zlatopolsky Persitz (1893-1969) was only 24-years old when she founded Omanut Press in Moscow, 1917, during that brief but heady period of Jewish cultural renaissance following the February Revolution. The daughter of one of the wealthiest Jews in Russia, Shoshana originally created Omanut as a means of bringing world literature into the treasury of the Hebrew language, but when her four-year-old son Gamliel died, she introduced a series of picture-books for children named the “Gamliel Library” after her son. Forced to move several times over the course of the next few years, from Moscow to Odessa and from Odessa to Frankfurt am Main, Shoshana nevertheless succeeded in producing some of the most beautiful children’s books ever printed in Hebrew. But up till now, scholars have been unsure of where, exactly, the books were first printed: in Odessa sometime around 1918 – or in Frankfurt am Main several years later? Now, thanks to books newly discovered in the Library of Congress, we are able to say that at least six of the picture-books were in fact published for the first time in Odessa. This article focuses on the creation of these beautiful books and the story behind their publication.